1993
DOI: 10.1002/er.4440170903
|View full text |Cite
|
Sign up to set email alerts
|

Steady-state simulation of vapour-compression heat pumps

Abstract: A vapour compression simulation model was developed. Simple mathematical models were employed for each component of the cycle. They resulted in a set of nonlinear equations, which was solved numerically. Heat losses from condenser to ambient were included. The model is capable of predicting the operating point of the system (including condensing and evaporating pressures) as a function of equipment characteristics (for example, compressor swept volume, speed and clearance ratio, and heat exchanger overall cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The model is based on quasi-steady state approach [7]. A set of nonlinear equations, involving heat, mass balances, heat transfer and equations for calculation of thermodynamic properties of working fluids, were utilized.…”
Section: Methodsmentioning
confidence: 99%
“…The model is based on quasi-steady state approach [7]. A set of nonlinear equations, involving heat, mass balances, heat transfer and equations for calculation of thermodynamic properties of working fluids, were utilized.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, the simulation results of a transcritical carbon dioxide heat pump system for dairy applications have been presented; in such systems simultaneous cooling and heating at 4 and 73 8C, respectively, is required. Although, the several simulation studies of conventional vapour compression system have been reported [5][6][7], such studies for transcritical CO 2 based systems are limited in number and scope. A CO 2 based air-conditioning system was simulated by Byon et al [8] employing assumed UA values for the heat exchangers; however, due to large variation in CO 2 properties in the heat exchanger and because of the transcritical nature of the cycle this rather simplifying assumption renders the model less realistic.…”
Section: Introductionmentioning
confidence: 98%
“…The heat load and COP for different flow rates of cooling water in the compression subsystem are displayed in Figure 10. As shown, the condenser temperature increases and the evaporator temperature maintains nearly constant with the decrease in the flow rate in the cooling water for the vapor compression chiller [27]. The improvement of the condenser temperature in the compression The heat load and COP for different flow rates of cooling water in the compression subsystem are displayed in Figure 10.…”
Section: Off-design Performancementioning
confidence: 88%
“…It can be inferred that the subcooling of the compression subsystem decreases in this condition. In addition, the condenser temperature increases with the increasing chilled water temperature [27]. Therefore, the abovementioned effect increases the R410A temperature in the subcooler and the consequent The heat load and COP for the different inlet temperatures of the chilled water are shown in Figure 8.…”
Section: Off-design Performancementioning
confidence: 96%